Bridging the discursive gap between lay and medical discourse in care coordination. Issue 7 (28th March 2017) - Sheaff, Rod; Halliday, Joyce; Byng, Richard; Øvretveit, John; Exworthy, Mark; Peckham, Stephen; Asthana, Sheena
Abstract: For older people with multiple chronic co‐morbidities, strategies to coordinate care depend heavily on information exchange. We analyse the information‐sharing difficulties arising from differences between patients' oral narratives and medical sense‐making; and whether a modified form of 'narrative medicine' might mitigate them. We systematically compared 66 general practice patients' own narratives of their health problems and care with the contents of their clinical records. Data were collected in England during 2012–13. Patients' narratives differed from the accounts in their medical record, especially the summary, regarding mobility, falls, mental health, physical frailty and its consequences for accessing care. Parts of patients' viewpoints were never formally encoded, parts were lost when clinicians de‐coded it, parts supplemented, and sometimes the whole narrative was re‐framed. These discrepancies appeared to restrict the patient record's utility even for GPs for the purposes of risk stratification, case management, knowing what other care‐givers were doing, and coordinating care. The findings suggest combining the encoding/decoding theory of communication with inter‐subjectivity and intentionality theories as sequential, complementary elements of an explanation of how patients communicate with clinicians. A revised form of narrative medicine might mitigate the discursive gap and its consequences for care coordination.